TEORIA CRÍTICA E EDUCAÇÃO NA ATUALIDADE: OLHARES PLURAIS (APRESENTAÇÃO) - Batista de Oliveira Silva, Luzia; Sander da Silva, Alex; da Silva Coelho, Allan (Revista Sul-Americana de Filosofia e Educação (RESAFE), 2018)
Apresentação do dossiê